2004
DOI: 10.1016/j.febslet.2004.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐symptomatic detection of prions by cyclic amplification of protein misfolding

Abstract: Transmissible spongiform encephalopathies (TSEs) are neurodegenerative disorders affecting humans and animals. At present, it is not possible to recognize individuals incubating the disease before the clinical symptoms appear. We investigated the effectiveness of the ''Protein Misfolding Cyclic Amplification'' (PMCA) technology to detect the protease-resistance disease-associated prion protein (PrP res ) in pre-symptomatic stages. PMCA allowed detection of PrP res in the brain of pre-symptomatic hamsters, enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 30 publications
4
98
0
Order By: Relevance
“…However, high-molecular-mass bands were observed in the amplified samples and may represent PrP aggregates or incomplete PK digestion. This was only observed when using PolyA to assist the PMCA reaction in this study but has been reported by others following PMCA without the addition of PolyA (Soto et al, 2005). No amplification of PrP Sc was observed in reaction mixtures containing only the CBH (Fig.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…However, high-molecular-mass bands were observed in the amplified samples and may represent PrP aggregates or incomplete PK digestion. This was only observed when using PolyA to assist the PMCA reaction in this study but has been reported by others following PMCA without the addition of PolyA (Soto et al, 2005). No amplification of PrP Sc was observed in reaction mixtures containing only the CBH (Fig.…”
Section: Resultsmentioning
confidence: 50%
“…PMCA has been reported previously to increase the sensitivity of the detection of PrP Sc from brains of experimentally scrapie-infected rodents (Saborio et al, 2001;Bieschke et al, 2004;Deleault et al, 2003), cattle and sheep naturally infected with bovine spongiform encephalopathy and scrapie, respectively (Soto et al, 2005), and more recently from humans with Creutzfeldt-Jakob disease (Jones et al, 2007) and deer with chronic wasting disease (Kurt et al, 2007). Furthermore, the application of this technology for the detection of PrP Sc in blood, both at terminal stages of disease and in pre-symptomatic animals Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PMCA allows an undetectable amount of PrP Sc to convert exogenously provided PrP C to PrP Sc after multiple cycles of sonication (11,33,40). Another study suggested that simple incubation without sonication is sufficient (41).…”
mentioning
confidence: 99%
“…In this method (Am-A-FACTT), an in vitro PrP Sc amplification step (Am) is included to further improve the detection limit. This methodology is based on the Protein Misfolding Cyclic Amplification (PMCA) which allows an undetectable amount of PrP Sc to convert exogenously provided PrP C to PrP Sc with [41][42][43] or without [44] multiple cycles of sonication. Similiarly, in the Am-A-FACTT, plasma or tissue homogenate from normal animals is incubated with infected samples to amplify PrP Sc in the sample.…”
Section: Prion Diseasementioning
confidence: 99%